2005
DOI: 10.1016/j.physc.2005.01.001
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy studies of MgB2 for valence state of Mg

Abstract: Core level X-ray Photoelectron Spectroscopy (XPS) studies have been carried out on polycrystalline MgB 2 pellets over the whole binding energy range with a view to having an idea of the charge state of Magnesium (Mg). We observe 3 distinct peaks in Mg 2p spectra at 49.3 eV (trace), 51.3 eV (major) and 54.0 eV (trace), corresponding to metallic Mg, MgB 2 and MgCO 3 or, divalent Mg species respectively. Similar trend has been noticed in Mg 2s spectra. The binding energy of Mg in MgB 2 is lower than that correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 18 publications
10
37
0
Order By: Relevance
“…The B1s spectrum before sputtering (t = 0) is composed of two peaks of similar intensity (BE = 192.4 and 187.8 eV) that are assigned to oxide and boride, respectively. Obtained BE values of Mg2p and B1s peaks are in good agreement with most of the literature data, [9][10][11] however they are noticeably higher than the values indicated in the paper by Vasquez et al [7] No theoretically predicted charge-transfer satellites [19] have been observed in Mg2p…”
Section: Films Deposited Using Cvdsupporting
confidence: 89%
See 3 more Smart Citations
“…The B1s spectrum before sputtering (t = 0) is composed of two peaks of similar intensity (BE = 192.4 and 187.8 eV) that are assigned to oxide and boride, respectively. Obtained BE values of Mg2p and B1s peaks are in good agreement with most of the literature data, [9][10][11] however they are noticeably higher than the values indicated in the paper by Vasquez et al [7] No theoretically predicted charge-transfer satellites [19] have been observed in Mg2p…”
Section: Films Deposited Using Cvdsupporting
confidence: 89%
“…[9][10][11] The MgKLL spectrum, registered at t = 0, also indicates the presence of two chemical species; magnesium oxide at KE = 1179.9 eV, and a low amount of magnesium boride at KE = 1182.5 eV. value of oxide is comparable with the reference sample and literature data, [18] while the KE values of boride differ from the reference samples, suggesting that the compound could be non-stoichiometric.…”
Section: Films Deposited Using Cvdsupporting
confidence: 68%
See 2 more Smart Citations
“…As it can be seen from the B 1s and Mg KLL spectra, the sample remained partially oxidized even after such a long time of intense sputtering, which can be explained [9,11,12] by the granular structure of the pressed powder. The signals of oxide [11,12] (BE = 193.3 eV) and boride [11 -13] (BE = 188.4 eV) can be easily separated by the peak fitting of the B 1s spectrum, while MgO and boride peaks are overlapped in Mg 2p line (∼51.0 eV). Therefore, it is rather difficult to determine the sample stoichiometry only from the XPS measurements.…”
Section: Reference Samplesmentioning
confidence: 99%